Polyester film and method for producing the same

JP2025023458APending Publication Date: 2025-02-17TORAY INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023127582
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-17

AI Technical Summary

Benefits of technology

【0012】 本発明によれば、フィルム製造工程中においてフィルムからのテレフタル酸揮発量を軽減することで、微小なテレフタル酸付着欠点を防止し、高品質かつ生産性に優れたポリエステルフィルムおよびその製造方法を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025023458000001
    Figure 2025023458000001
  • Figure 2025023458000002
    Figure 2025023458000002
  • Figure 2025023458000003
    Figure 2025023458000003
Patent Text Reader

Abstract

To provide a polyester film which can reduce a terephthalic acid volatilization amount from a film in a film production step, prevents fine terephthalic acid adhesion defects, has high quality and is excellent in productivity, and a method for producing the same.SOLUTION: A polyester film has a base material layer containing a polyester resin as a main component, has thickness of 1 μm or more, and satisfies all the following (1) to (5), wherein when the layer containing the polyester resin as the main component is represented by an S1 layer, at least one outermost surface layer of the base material layer is the S1 layer. Expression (1): 15 ppm≤phosphorus element content (mass basis)≤80 ppm, Expression (2): 4 ppm≤sodium element content (mass basis)≤40 ppm, Expression (3): 5 ppm≤manganese element (mass basis)≤40 ppm, Expression (4): antimony element content (mass basis)≤5 ppm, and Expression (5): 14 ppm≤metal element content (mass basis)≤100 ppm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a high-quality polyester film having fewer minute adhesion defects caused by condensation and dropping of volatile components from polyester resin, and a method for producing the same. [Background technology]

[0002] Polyester films have excellent mechanical properties, thermal properties, chemical resistance, electrical properties, and moldability, and are used for a variety of applications. Among polyester films, polyethylene terephthalate (hereinafter sometimes referred to as PET) films have excellent transparency and processability, and are therefore particularly suitable for use as process films when manufacturing electronic components and display materials.

[0003] Generally, when polyester film is used as a process material for manufacturing other parts or products, a widely used method is to laminate various molten resins or solutions containing resins on its surface, and then in a subsequent process, the resin laminated on the polyester film is solidified to stabilize the structure, and then the polyester film is peeled off. In this method, the polyester film not only serves as a support, but also transfers its surface shape to the material surface to form a stable surface state.

[0004] In addition, due to its excellent dimensional stability, solvent resistance, and surface uniformity, polyester film is also suitable for use as an optical compensation film for various displays, and as a release film for products that require extremely high quality control, such as the formation of thin insulating layers of submicron order used in multilayer ceramic capacitors (MLCCs). In particular, for these applications, the demand for high-definition displays and miniaturization and high reliability of MLCCs has been growing in recent years, and there is a strong demand for defect-free films. In particular, there is a strong demand for the improvement of minute foreign matter attached to the surface of polyester film, which may induce fatal defects on the surface of components formed on the polyester film, as an urgent issue.

[0005] The most serious problem of foreign matter adhering to the surface of polyester film is the terephthalic acid defect, which occurs when the terephthalic acid component volatilizes during the polyester film manufacturing process and recondenses, adhering as minute foreign matter. In particular, defects that volatilize during the thermal crystallization process in an oven, recondense on the inner walls of the oven, and then adhere to the film are problematic. Since the volatilized terephthalic acid adheres to all parts through the air circulation system of the oven, it is difficult to completely remove the defects by cleaning the inside of the oven, and improving this problem is a major issue.

[0006] Furthermore, with the growing demand for reducing the environmental impact, it has become necessary to utilize recycled materials regenerated from films in order to reduce energy consumption and CO2 emissions. In particular, process films do not remain in the final product, but are peeled off at the early stages of the product manufacturing process, and tend to be processed to a low degree, so are often discarded in a state that is relatively easy to recycle. Therefore, there is a strong demand for process films to reduce the environmental impact through reuse. On the other hand, recycled materials have a high thermal history, so they are prone to developing the attached terephthalic acid defect, and there is growing expectation for films that combine environmental reduction with high quality.

[0007] In response to the above-mentioned problems, the following studies have been carried out. For example, Patent Documents 1 and 2 disclose a technique for reducing linear oligomers by adding an ionic compound composed of specific phosphorus and sulfur elements. Patent Document 3 discloses a method of using a specific catalyst and carrying out a deactivation treatment after the completion of polymerization, and a method of including isophthalic acid as a copolymerization component. Patent Document 4 describes a method of adding a specific ionic liquid to dissolve linear oligomers containing terephthalic acid in a resin and prevent volatilization. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent Publication No. 2023-15002 [Patent Document 2] JP 2022-89784 A [Patent Document 3] International Publication No. 2018 / 092414 [Patent Document 4] International Publication No. 2016 / 177084 Summary of the Invention [Problem to be solved by the invention]

[0009] However, the methods described in Patent Documents 1 and 2 have the effect of reducing the amount of terephthalic acid generated, but are unable to achieve the high quality required for the above-mentioned applications. The method described in Patent Document 3 is a technology that enables the suppression of the amount of volatilization by dissolving linear oligomers containing terephthalic acid with an added ionic liquid, but the effect is insufficient and the desired quality level cannot be achieved. In addition, Patent Document 4 can effectively suppress the generation of terephthalic acid, especially when isophthalic acid is copolymerized, but copolymerization of isophthalic acid deteriorates heat resistance and chemical resistance, so there is a problem that the properties required for a process film are hindered. In addition, although it is effective in suppressing die lines in the extrusion process, the effect of reducing the volatilized terephthalic acid component in the subsequent thermal crystallization process is insufficient. Furthermore, the intrinsic viscosity (IV) is high, making it difficult to perform high-precision filtration required for high-quality process films, and there are also problems such as the inability to remove foreign matter inside the film and the increase in internal defects.

[0010] The present invention aims to solve these problems and provide a polyester film that is high quality and has excellent productivity, and a method for producing the same, by reducing the amount of terephthalic acid volatilized from the film during the film production process, thereby preventing minute terephthalic acid adhesion defects. [Means for solving the problem]

[0011] The present invention aims to solve the above problems. [I]. A polyester film having a base layer containing a polyester resin as a main component, a thickness of 1 μm or more, and satisfying all of the following (1) to (5), and characterized in that when the layer containing a polyester resin as a main component is an S1 layer, at least one outermost layer of the base layer is the S1 layer. 15 ppm or less Phosphorus content (by mass) or less 80 ppm (1) 4 ppm or less Sodium content (by mass) or less than 40 ppm (2) 5ppm≦Manganese element content (by mass)≦40ppm (3) Antimony element content (by mass) ≦ 5 ppm (4) 14ppm≦Metal element content (mass basis)≦100ppm (5) [II]. The polyester film according to [I], wherein the S1 layer satisfies the following (6): 5ppm≦Germanium element content (by mass)≦80ppm (6) [III]. The polyester film according to [I] or [II], wherein at least a part of the phosphorus element is derived from phosphoric acid and sodium phosphate. [IV]. The polyester film according to any one of [I] to [III], wherein the base layer has the S1 layer and a layer (S2 layer) located on the outermost surface opposite to the S1 layer, and the S2 layer satisfies all of the above (1) to (5). [V]. The polyester film according to any one of [I] to [IV], wherein the base layer comprises the S1 layer, a layer (S2 layer) located at the outermost surface opposite the S1 layer, and one or more layers (I layers) located between the S1 layer and the S2 layer. [VI]. The polyester film according to [V], wherein at least one of the layers I contains recycled materials mainly composed of polyester resin. [VII]. The polyester film according to [VI], wherein the recycled materials include self-recovered materials. [VIII]. The polyester film according to any one of [I] to [VII], which has a functional layer on at least one surface of the base layer. [IV] A method for producing the polyester film according to any one of [I] to [VIII], wherein the S1 layer is formed using a polyester resin having a terephthalic acid volatilization amount (T) of less than 100 ppm, where the terephthalic acid volatilization amount (T) is the amount (by mass) of terephthalic acid volatilized when heat-treated at a temperature of 290° C. for 20 minutes. [X]. A method for producing a polyester film according to any one of [V] to [VIII], in which the S1 layer, the S2 layer, and the I layer are formed using a polyester resin that satisfies all of the following (7) to (9): Ts1 <Ti (7) Ts2 <Ti (8) Ti≦350ppm (9) Ts1: The amount of terephthalic acid volatilized from the polyester resin constituting the S1 layer (T) Ts2: The amount of terephthalic acid volatilized from the polyester resin constituting the S2 layer (T) Ti: The amount of terephthalic acid volatilized from the polyester resin constituting the I layer (T) Here, the volatilized amount of terephthalic acid (T) is the amount (mass basis) of terephthalic acid volatilized when heat-treated at a temperature of 290° C. for 20 minutes, and when the I layer is composed of multiple layers, the volatilized amount of terephthalic acid (T) is calculated as the weighted average value of the multiple layers. [XI]. The method for producing a polyester film according to [X], wherein the melt resistivity of the polyester resin constituting the S1 layer and the polyester resin constituting the S2 layer are both higher than 10.0 MΩ cm, and the melt resistivity of the polyester resin constituting the I layer is 10.0 MΩ cm or less. Effect of the Invention

[0012] According to the present invention, by reducing the amount of terephthalic acid volatilized from a film during the film production process, minute defects of terephthalic acid adhesion can be prevented, and a high-quality polyester film and a production method thereof that are excellent in productivity can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention will be described in detail below. The polyester film of the present invention is a polyester film having a base layer mainly composed of a polyester resin, a thickness of 1 μm or more, and satisfying all of the following (1) to (5), and when the layer mainly composed of a polyester resin is defined as an S1 layer, at least one of the outermost layers of the base layer is the S1 layer. 15 ppm or less Phosphorus content (by mass) or less 80 ppm (1) 4 ppm or less Sodium content (by mass) or less than 40 ppm (2) 5ppm≦Manganese element content (by mass)≦40ppm (3) Antimony element content (by mass) ≦ 5 ppm (4) 14ppm≦Metal element content (mass basis)≦100ppm (5).

[0014] The polyester film of the present invention has a base layer mainly composed of a polyester resin. In the present invention, the polyester resin refers to a resin having a molecular structure in which dicarboxylic acid units and diol units are repeatedly linked by ester bonds, and the polyester film refers to a sheet-shaped molded body mainly composed of a polyester resin. Details of the polyester resin that can be suitably used for the polyester film of the present invention will be described later. The main component refers to a component that is contained in an amount of more than 50 mass% and 100 mass% or less when the total components of the target object are taken as 100 mass%. The base layer mainly composed of a polyester resin refers to a layer that has a polyester resin as the main component and has a thickness of 1 μm or more (hereinafter, the "base layer mainly composed of a polyester resin" may be simply referred to as the "base layer"). The base layer may have a single layer structure or a laminate structure, and when layers that satisfy the above requirements are laminated in succession, the entire layer is treated as one base layer. The upper limit of the thickness of the base layer is not particularly limited, but is usually 500 μm or less in terms of productivity and handling during use. When the polyester film is used as a process film, the thickness is preferably from 6 μm to 188 μm, particularly preferably from 12 μm to 100 μm, in view of the balance of strength, stability, and handleability of the polyester film.

[0015] The polyester film of the present invention has a thickness of 1 μm or more, satisfies all of the following (1) to (5), and when a layer containing a polyester resin as a main component is defined as the S1 layer, the outermost layer of at least one of the base layers is the S1 layer. When the polyester film has a single layer structure, the layer can be considered to have an S1 layer as long as it has a thickness of 1 μm or more, satisfies all of the following (1) to (5), and contains a polyester resin as a main component. 15 ppm or less Phosphorus content (by mass) or less 80 ppm (1) 4 ppm or less Sodium content (by mass) or less than 40 ppm (2) 5ppm≦Manganese element content (by mass)≦40ppm (3) Antimony element content (by mass) ≦ 5 ppm (4) 14ppm≦Metal element content (mass basis)≦100ppm (5).

[0016] By adopting such an embodiment, it is possible to effectively suppress the volatilization of the terephthalic acid component during the polyester film production process. If the thickness of the layer corresponding to the S1 layer is less than 1 μm, the effect of suppressing the volatilization of terephthalic acid becomes insufficient.

[0017] In addition, the polyester film of the present invention is also preferably configured such that the base layer has an S1 layer and a layer (S2 layer) located on the outermost surface opposite to the S1 layer, and the S2 layer satisfies all of the above (1) to (5), because this further reduces the volatile components of terephthalic acid. In the above embodiment, the polyester film has a laminated structure consisting of at least two layers (S1 layer and S2 layer). Note that, hereinafter, the above (1) to (5) will be described using the S1 layer as an example, but they also apply to the S2 layer unless otherwise specified. In addition, it is preferable that the S2 layer is mainly composed of a polyester resin, and its composition may be the same as or different from that of the S1 layer.

[0018] When the base layer of the polyester film is a laminated structure of two or more layers, the upper limit of the thickness of the S1 layer is not particularly limited, but in consideration of the film productivity, production cost, and the purpose of making the base layer a laminated structure, such as controlling the surface roughness and imparting adhesiveness, it is preferable that it is 10 μm. In addition, the thickness of the S2 layer is also preferably 1 μm or more from the above viewpoint. The upper limit of the thickness of the S2 layer is not particularly limited, but it is preferable to adjust the thickness of the polyester film to 188 μm or less from the balance of the strength, stability, and handleability of the polyester film.

[0019] It is more preferable that the polyester film of the present invention is composed of an S1 layer, a layer (S2 layer) located on the outermost surface opposite to the S1 layer, and one or more layers (I layer) located between the S1 layer and the S2 layer. By forming a laminated structure including the I layer, which is an intermediate layer, the shape stability of the film surface, which is the most important aspect of a process film, is ensured by the S1 layer and the S2 layer, while recycled raw materials can be used for the I layer, or a polyester resin with improved electrostatic applicability in the casting process can be used to increase productivity, thereby expanding the range of polyester film design, and it is possible to suitably achieve the properties required for various polyester films. The I layer may be a single layer or may be composed of two or more layers.

[0020] The S1 layer in the base layer of the polyester film of the present invention must contain phosphorus element in an amount of 15 ppm or more and 80 ppm or less by mass. The lower limit is more preferably 20 ppm, and even more preferably 25 ppm. The upper limit is preferably 60 ppm, and more preferably 50 ppm. By setting the phosphorus element amount within the above range, the thermal decomposition of the polyester resin can be suppressed, so that it is possible to reduce the amount of terephthalic acid volatilized during heating and the amount of internal foreign matter when the polyester film is made. The method for measuring the amount of phosphorus element will be described later (the same applies to the amounts of other elements). In addition, the term "mass basis" means that the total components constituting the S1 layer are used as the basis, and can be interpreted in the same manner hereinafter.

[0021] The S1 layer in the base layer of the polyester film of the present invention must contain sodium element in an amount of 4 ppm or more and 40 ppm or less by mass. The upper limit is preferably 30 ppm, more preferably 20 ppm. By setting the sodium element in the above range, the generation of foreign matter caused by sodium element is reduced, and the thermal decomposition of the polyester resin is suppressed, thereby making it possible to reduce the amount of terephthalic acid volatilized during heating. In addition, by using sodium element in combination with phosphorus element, the hydrolysis property of the polyester resin in particular can be significantly reduced, and the amount of terephthalic acid volatilized during heating can be more effectively reduced.

[0022] In particular, the sodium element and the phosphorus element are preferably prepared using phosphoric acid and sodium phosphate from the viewpoint of suppressing decomposition of the polyester resin. That is, in the polyester film of the present invention, it is preferable that at least a part of the phosphorus element contained in the S1 layer is derived from at least one of phosphoric acid and sodium phosphate. When phosphate ions and sodium ions or sodium phosphate are present in the S1 layer, the phosphorus element contained in the S1 layer is deemed to be "derived from at least one of phosphoric acid and sodium phosphate."

[0023] In order to enhance the deterioration suppression (hydrolysis resistance) effect of the polyester resin of the S1 layer, it is preferable to add phosphoric acid and sodium phosphate to the polyester resin that is the raw material of the base layer, and it is more preferable to make the contents of these components closer to equal amounts in terms of molar ratio. That is, in the polyester film of the present invention, it is preferable that the S1 layer contains both phosphorus element derived from phosphoric acid and phosphorus element derived from sodium phosphate, and it is more preferable to make the amounts of both closer to equal amounts in terms of molar ratio.

[0024] The S1 layer in the base layer of the polyester film of the present invention must contain manganese element in an amount of 5 ppm to 40 ppm by mass. The lower limit is preferably 10 ppm. The upper limit is preferably 30 ppm. Since manganese compounds have the effect of suppressing thermal decomposition of polyester resins, particularly oxidative decomposition mediated by oxygen, by making the amount of manganese compound equal to or greater than the lower limit, it is possible to reduce the amount of terephthalic acid volatilized from polyester resins. However, since manganese element has catalytic activity even in heat treatment at a relatively low temperature below the melting point of polyester resins, such as in the film stretching process, it is necessary to make the amount equal to or less than the upper limit in order to suppress an increase in the amount of terephthalic acid volatilized during the manufacturing process.

[0025] The S1 layer in the base layer of the polyester film of the present invention has a total content of metal elements of 14 ppm or more and 100 ppm or less, preferably 80 ppm or less, based on mass. If the amount of metal elements in the base layer exceeds 100 ppm, the polyester chain is promoted to be cut in the melt extrusion process, so that gelled products having a three-dimensional structure are generated frequently, and the amount of volatilization of terephthalic acid increases in the film manufacturing process, thereby degrading the quality of the film. In addition, there is also a problem that defects in the film are increased due to precipitation of the metal component itself or a complex of the metal component and other chemical substances. In addition, the metal element referred to here is synonymous with the metal element generally defined, and refers to all elements of Groups 1, 2 to 12 except hydrogen in the periodic table of elements, Groups 13 from the third period onwards except boron, Groups 14 from the fourth period onwards except carbon and silicon, Groups 15 from the fifth period onwards, and Group 16 of the sixth period. The lower limit of the metal element content in the S1 layer of the polyester film is substantially 14 ppm, based on the lower limits of the manganese element and sodium element contents and the necessary amounts of other usable metal catalysts.

[0026] The S1 layer in the base layer of the polyester film of the present invention must contain 5 ppm or less of antimony element by mass, preferably 3 ppm or less, and more preferably no antimony element. Antimony compounds are widely used as polycondensation catalysts for polyester resins, but they have the problem of being easily precipitated in the film as metallic foreign matter. In addition, in order to function as a catalyst, it is necessary to add at least 50 ppm or more, but if the amount of antimony element is added in an amount of 50 ppm or more, the amount of volatilization of terephthalic acid during heating tends to increase. It is preferable that the S1 layer does not contain antimony element at all, but a small amount may be mixed in due to contamination of catalyst components used in other polyester resins, such as when multiple types of polyester films are produced in the same manufacturing equipment. However, in the present invention, the content is 5 ppm or less, so that the effect on the quality of the polyester resin and polyester film can be within an acceptable range.

[0027] By having an S1 layer that satisfies all of the above (1) to (5) (preferably by forming an S1 layer that satisfies all of the above (1) to (5) using a polyester resin that satisfies all of the above (1) to (5)), it is possible to reduce all of the thermal decomposition, hydrolysis, and oxidative decomposition of the polyester resin. As a result, it is possible to suppress the decomposition of the polyester resin in the polyester film manufacturing process, such as the melting process, stretching process, and thermal crystallization process. By reducing the decomposition in the melting process and thermal crystallization process, which are particularly high in temperature, it is possible to reduce the amount of terephthalic acid contained inside the polyester film. As a result, the amount of volatilized terephthalic acid in the thermal crystallization process is reduced, making it possible to suppress the occurrence of minute terephthalic acid adhesion defects on the polyester film surface.

[0028] The S1 layer in the base layer of the polyester film of the present invention preferably contains germanium element in an amount of 5 ppm or more and 80 ppm or less by mass. The upper limit is more preferably 50 ppm. The germanium compound is used as a polymerization catalyst for polyester resin, and by setting the amount to the above-mentioned lower limit or more, it is possible to proceed with the polycondensation reaction without delay, and the amount of volatilization of terephthalic acid and the generation of internal foreign matter when the polyester film is made can be reduced. In addition, germanium element has excellent catalytic activity, and if it is present in excess, it promotes thermal decomposition, oxidative decomposition, and hydrolysis of polyester resin, so it is preferable to set it to the above-mentioned upper limit or less.

[0029] The polyester film of the present invention may have a functional layer on at least one surface of the base layer for the purpose of improving adhesion with the functional layer formed on the surface, imparting releasability, imparting slipperiness and antistatic properties to the film, etc. The method for laminating these functional layers is not particularly limited, but a coating method is preferred because various functional layers can be laminated relatively easily and uniformly.

[0030] In the polyester film of the present invention, the coating method for forming the functional layer is not particularly limited. For example, a so-called off-line coating method can be used in which a coating composition for forming a functional layer is applied and dried on a film unwound in a separate process from the film production process, or a so-called in-line coating method can be used in which a coating composition for forming a functional layer is applied during a process in which a resin is extruded by an extruder and the resin is formed into a sheet to form a film, thereby obtaining a coated film in one go.

[0031] A lubricant is preferably added to the functional layer of the polyester film of the present invention in order to improve the surface slipperiness and improve the handling. The lubricant used is not particularly limited as long as it does not impair the film properties, and examples thereof include inorganic particles such as colloidal silica, titanium oxide, aluminum oxide, zirconium oxide, calcium carbonate, carbon black, and zeolite particles, and organic particles such as acrylic particles, silicone particles, polyimide particles, "Teflon" (registered trademark) particles, crosslinked polyester particles, crosslinked polystyrene particles, crosslinked polymer particles, and core-shell particles. Any of these particles may be used, or a combination of two or more types may be used. The number average primary particle size of these particles (hereinafter, sometimes simply referred to as the average primary particle size) is preferably within the range of 50 to 1000 nm. Here, the average primary particle size is the average particle size of primary particles defined in JIS H7008 (2002) as particles generated by the growth of a single crystal nucleus. The amount of particles added should be appropriately adjusted and designed depending on the thickness of the lubricious layer, the resin composition, the average primary particle size, the desired lubricity, and the application, but is preferably in the range of 0.05 to 8 mass%, and more preferably in the range of 0.1 to 5 mass%, when the total components forming the functional layer are taken as 100 mass%.

[0032] In order to impart various functions such as retaining lubricant particles, improving adhesion with other functional layers, and sealing oligomers precipitated from the film, the coating composition for forming the functional layer of the polyester film of the present invention may contain known polyester, acrylic, urethane, epoxy, and other resins, antistatic agents, release agents, ultraviolet absorbers, etc., either alone or in combination. Furthermore, the coating composition may contain a melamine, oxazoline, or carbodiimide crosslinking agent.

[0033] When the polyester film of the present invention is used as a process film, it is preferable that the film surface has a release layer that facilitates peeling. Compounds that exhibit a release function generally include silicone compounds, fluorine compounds, wax compounds, etc., but there is a problem that some of the components are transferred and the product is easily contaminated. Therefore, it is preferable to use a long-chain alkyl resin in the polyester film of the present invention. The long-chain alkyl resin is a resin in which a long-chain alkyl group is covalently bonded to the main skeleton, and is preferable in that it can impart good peelability. When a long-chain alkyl resin is used, the long-chain alkyl group with low surface free energy segregates on the surface of the release layer, and is oriented and crystallized in a direction perpendicular to the surface. As a result, the terminal methyl group is exposed to the surface, and the surface free energy is reduced, thereby exhibiting light peelability.

[0034] Furthermore, the long-chain alkyl resin is more preferably a block copolymer consisting of units having a long-chain alkyl group. When the release agent is a block copolymer consisting of units having a long-chain alkyl group, the long-chain alkyl group is easily oriented. There is no particular limitation on the method for producing the block copolymer as long as it is a living radical polymerization method other than the atom transfer radical polymerization method (ATRP method), and various polymerization methods such as reversible addition-fragmentation chain transfer polymerization method (RAFT method), polymerization method using an organotellurium compound (TERP method), polymerization method using an organoantimony compound (SBRP method), polymerization method using an organobismuth compound (BIRP method), and living radical polymerization method of exchange chain mechanism such as iodine transfer polymerization method, and nitroxy radical method (NMP method) can be adopted. Among these, the RAFT method and the NMP method are preferable from the viewpoint of controllability of polymerization and ease of implementation.

[0035] The ratio of the long-chain alkyl group-containing monomer to the long-chain alkyl group-free monomer in the long-chain alkyl resin is preferably 50 to 99% by molar ratio, more preferably 60 to 97%, and even more preferably 70 to 95%. By setting the long-chain alkyl group-containing monomer to the above ratio, when the coating composition for forming the release layer contains at least one resin selected from, for example, polyester resin, acrylic resin, and urethane resin, the compatibility of the long-chain alkyl resin with these resins is increased, and a uniform release layer can be formed.

[0036] In order to achieve both the quality of the film and the reduction of energy consumption and the amount of CO2 generated, the polyester film of the present invention preferably contains a recycled raw material mainly composed of a polyester resin in at least one of the I layers, and more preferably the recycled raw material contains a self-recovered raw material. Here, the recycled raw material refers to a recycled polyester raw material obtained by regenerating a part of a polyester film that was not made into a product during the manufacturing process, or a polyester film or a polyester molded body after use. When using a recycled raw material derived from a polyester film, the recycled raw material can be used to manufacture a base layer of the same polyester film, or a base layer of a different polyester film. When a base layer of the same polyester film is manufactured using a recycled raw material derived from a polyester film, the recycled raw material is called a self-recovered raw material. Note that, when a base layer of the same polyester film is manufactured using a recycled raw material, there is a possibility that a slight difference in composition may occur compared to when a recycled raw material is not used, but if the composition of the base layer of the polyester film from which the recycled raw material is derived and the base layer of the resulting polyester film are 95% or more the same on a mass basis, the two are treated as "base layers of the same polyester film".

[0037] In recent years, with the rise in environmental awareness, there is a strong demand for reducing energy consumption and CO2 emissions, and in order to achieve this, it is effective to use recycled materials for the base layer of polyester film. In particular, to realize a recycling-oriented society, it is preferable to use recycled materials regenerated from the film itself, i.e., self-recovered materials.

[0038] In the recycled raw material for the polyester film of the present invention, when the polyester film has a functional layer on the surface, it is preferable to remove the functional layer before using it as the recycled raw material from the viewpoint of removing foreign matter. By using recycled raw material from which the functional layer has been removed, it is possible to prevent various resins, additives, etc. contained in the functional layer from being mixed into the base layer of the polyester film, thereby suppressing an increase in the number of defects inside the obtained polyester film and reducing quality problems. In other words, a preferred feature of the manufacturing method for the polyester film of the present invention is the use of recycled raw material from which the functional layer has been removed from a polyester film provided with a functional layer.

[0039] The polyester resin, which is the main component of the base layer in the polyester film of the present invention, is preferably polyethylene terephthalate (PET) in order to sufficiently increase heat resistance. In addition, a copolymer component may be contained within a range that does not impair the effects of the present invention. Polyethylene terephthalate refers to a polyester resin whose main structural unit is an ethylene terephthalate unit, and the main structural unit refers to a structural unit contained in more than 50 mol% when all structural units constituting the molecular chain of the resin are 100 mol%. Note that the same can be interpreted for other polyester resins below, except that the main structural unit is replaced.

[0040] The base layer in the polyester film of the present invention is not particularly limited as long as it is mainly composed of polyester resin, but is preferably a biaxially oriented polyester film. The term "biaxial orientation" as used herein refers to a film that shows a biaxially oriented pattern in wide-angle X-ray diffraction. A biaxially oriented polyester film can generally be obtained by stretching an unstretched polyester sheet by about 2.5 to 5.0 times in each of the longitudinal and transverse directions of the sheet, and then subjecting the sheet to heat treatment to complete the crystal orientation. The longitudinal direction refers to the direction in which the film runs during the manufacturing process (in the case of a film roll, this corresponds to the winding direction, also called the vertical direction), and the transverse direction (also called the horizontal direction) refers to the direction perpendicular to the longitudinal direction within the film plane.

[0041] Next, a method for producing the polyester resin used in the S1 layer of the polyester film according to the present invention will be described. When the base layer includes an S2 layer or an I layer, the polyester resin can also be used in these layers. The method for producing the polyester resin uses a dicarboxylic acid component or its ester and a diol component as main raw materials and consists of the following two-stage process. That is, the first stage is (A) an esterification reaction or (B) an ester exchange reaction, and the second stage is (C) a polycondensation reaction.

[0042] As raw materials for producing the polyester resin used in the S1 layer of the polyester film of the present invention, dicarboxylic acids or dicarboxylic acid esters and diols can be used, and these can also be used in combination of two or more kinds.

[0043] Examples of dicarboxylic acid components that can be used in the production of polyester resins include terephthalic acid, 2,6-naphthalenedicarboxylic acid, isophthalic acid, diphenyl-4,4'-dicarboxylic acid, 5-sodium sulfoisophthalic acid, oxalic acid, succinic acid, adipic acid, sebacic acid, malonic acid, and dimer acid. Examples of dicarboxylic acid esters include the lower alkyl esters, acid anhydrides, and acyl chlorides of the above-mentioned dicarboxylic acids, and methyl esters, ethyl esters, and hydroxyethyl esters are preferably used. These components may be used alone or in combination.

[0044] In the polyester resin used in the S1 layer of the polyester film of the present invention, more preferred embodiments of the dicarboxylic acid or dicarboxylic acid ester are terephthalic acid, 2,6-naphthalenedicarboxylic acid, isophthalic acid, or alkyl esters thereof, since they can give a polyester resin having a high melting point and which is easily processable into a film, and these can also be used in appropriate combinations.

[0045] Examples of diols that can be used in the production of polyester resins include aliphatic diols such as ethylene glycol, 1,2-propanediol, 1,3-propanediol, butanediol, 2-methyl-1,3-propanediol, hexanediol, and neopentyl glycol; alicyclic diols include saturated alicyclic primary diols such as cyclohexanedimethanol, cyclohexanediethanol, norbornanedimethanol, norbornanediethanol, tricyclodecanedimethanol, tricyclodecanediethanol, decalindimethanol, and decalindiethanol; and saturated heterocyclic primary diols containing cyclic ethers such as isosorbide. Other examples include various alicyclic diols such as cyclohexanediol, bicyclohexyl-4,4'-diol, 2,2-bis(4-hydroxycyclohexylpropane), 2,2-bis(4-(2-hydroxyethoxy)cyclohexyl)propane, cyclopentanediol, 3-methyl-1,2-cyclopentadiol, 4-cyclopentene-1,3-diol, and adamantanediol, and aromatic diols such as paraxylene glycol, bisphenol A, bisphenol S, styrene glycol, 9,9-bis(4-(2-hydroxyethoxy)phenyl)fluorene, and 9,9'-bis(4-hydroxyphenyl)fluorene.

[0046] These components may be used alone or in combination, and polyfunctional alcohols such as trimethylolpropane and pentaerythritol may also be used other than the diol within the scope of not impairing the effects of the present invention. It is preferable to use ethylene glycol as the diol, since it is possible to fully achieve the effects of the present invention and to obtain a polyester resin that is easily processed into a film.

[0047] In the manufacturing method of the polyester resin used in the S1 layer of the polyester film of the present invention, the (A) esterification reaction step in the first step is a step of esterifying a dicarboxylic acid with a diol at a predetermined temperature until a predetermined amount of water is distilled to obtain a low polymer. When obtaining a low polymer by esterification reaction, the molar ratio of dicarboxylic acid to diol (diol / dicarboxylic acid) before the start of the esterification reaction is preferably in the range of 1.05 to 1.40 from the viewpoint of esterification reactivity and heat resistance. More preferably, it is in the range of 1.05 to 1.30, and even more preferably, it is in the range of 1.05 to 1.20. By setting it in the above range, it has good reactivity and can suppress the generation of by-products such as dimers of diol, so that the heat resistance can be improved.

[0048] The (B) transesterification step is a step of transesterifying a dicarboxylic acid alkyl ester with a diol until a predetermined amount of alcohol is distilled to obtain a low polymer. When a low polymer is obtained by transesterification, the molar ratio of the dicarboxylic acid alkyl ester to the diol (diol / dicarboxylic acid alkyl ester) is preferably in the range of 1.7 to 2.3 from the viewpoints of reactivity and heat resistance. By setting the ratio in the above range, the transesterification reaction can be efficiently progressed and the by-production of a dimer of the diol can be suppressed, thereby improving the heat resistance.

[0049] In the second step, the polycondensation reaction (C) is a step for obtaining a polyester resin from the low polymer obtained by the esterification reaction (A) or the transesterification reaction (B).

[0050] The polyester resin used in the S1 layer of the polyester film of the present invention can be produced by any of batch polymerization, semi-continuous polymerization, and continuous polymerization.

[0051] In the method for producing the polyester resin used in the S1 layer, the catalyst used in the (A) esterification reaction may be a compound such as manganese, cobalt, zinc, titanium, or calcium, but it is preferable to carry out the esterification reaction without a catalyst from the viewpoint of thermal decomposition and generation of foreign matter in the polycondensation reaction stage. Here, the (A) esterification reaction proceeds sufficiently even without a catalyst due to the autocatalytic action of the carboxylic acid. In addition, a known transesterification catalyst can be used as the catalyst used in the (B) transesterification reaction. Examples of the transesterification catalyst include organic manganese compounds, organic magnesium compounds, organic calcium compounds, organic cobalt compounds, and organic lithium compounds, and specific examples thereof include carbonates, acetates, benzoates, oxides, and hydroxides, but are not limited thereto.

[0052] In the manufacturing method of the polyester resin used in the S1 layer of the polyester film of the present invention, the compound containing phosphorus, manganese, sodium and germanium may be added at any stage of the (A) esterification reaction or (B) ester exchange reaction process, or the subsequent (C) polycondensation reaction process. However, by adding the compound before the end of the polycondensation reaction, decomposition of the polyester resin can be suppressed and a polyester resin with less foreign matter can be obtained.

[0053] In the method for producing the polyester resin used in the S1 layer of the polyester film of the present invention, it is preferable to add a compound containing phosphorus, manganese and sodium before the end of the polycondensation reaction, and to make the contents thereof satisfy the following formulas (10) to (12) with respect to the finally obtained polyester resin. By adopting such an embodiment, it becomes easy for the S1 layer of the obtained polyester film to satisfy the formulas (1) to (3). When the base layer is produced by mixing the polyester resin with another resin, in the following formulas (10) to (12), "mass ratio relative to the polyester resin" should be interpreted as "mass ratio relative to the polyester resin composition for producing the S1 layer (or other layer if used in another layer)". 15ppm≦Phosphorus content (by mass)≦80ppm (10) 4ppm≦Sodium content (by mass)≦40ppm (11) 5ppm≦Manganese element content (by mass)≦40ppm (12) The compound containing manganese element used in the polyester resin used in the S1 layer of the polyester film of the present invention is not particularly limited, but examples thereof include manganese acetate, manganese nitrate, manganese chloride, manganese sulfate, and their hydrates, and manganese acetate is preferred from the viewpoint of solubility and catalytic activity. These compounds can be used alone or in combination. The form of the compound containing manganese element when added may be any of powder, slurry, and solution, and it is preferred to add it as a solution from the viewpoint of dispersibility. The solvent used at this time is preferably the same as the diol component of the polyester resin. For example, in the case of PET, it is particularly preferred to use ethylene glycol as the solvent.

[0054] The compound containing sodium element used in the production of the polyester resin used in the S1 layer of the polyester film of the present invention is not particularly limited. For example, sodium phosphate, hydroxide, acetate, carbonate, nitrate, chloride, etc. can be used. From the viewpoint of heat resistance, the compound containing sodium element is more preferably sodium phosphate. Examples of sodium phosphate include sodium dihydrogen phosphate, disodium hydrogen phosphate, and trisodium phosphate. From the viewpoint of heat resistance, sodium dihydrogen phosphate is particularly preferable. In addition, multiple sodium phosphates may be used in combination.

[0055] In addition, in the production of the polyester resin used in the S1 layer of the polyester film of the present invention, it is preferable to use the above-mentioned sodium phosphate in combination with another compound containing phosphorus, and it is particularly preferable to mix them as a buffer solution consisting of sodium phosphate and phosphoric acid. By adding the buffer solution consisting of sodium phosphate and phosphoric acid, it is possible to exhibit better heat resistance.

[0056] In addition, an alkali metal compound other than sodium phosphate may be used in combination within the range of the above-mentioned sodium element content. For example, by using potassium hydroxide in combination, the melt resistivity of polyester required for electrostatic application film formation in film production can be reduced, thereby improving productivity.

[0057] The sodium-containing compound may be added in the form of powder, slurry, or solution, and is preferably added as a solution from the viewpoint of dispersibility. The solvent used in this case is preferably the same as that of the diol component of the polyester resin, and in the case of PET, ethylene glycol is particularly preferred.

[0058] In the method for producing the polyester resin for the S1 layer of the polyester film according to the present invention, it is preferable to add germanium element so that the content is 5 ppm or more and 80 ppm or less relative to the mass of the polyester resin. The lower limit is preferably 10 ppm. The upper limit is preferably 50 ppm. Compounds containing germanium element used in the production of the polyester resin include, but are not limited to, germanium oxides and germanium alkoxides. These compounds can be used alone or in combination.

[0059] In the method for producing the polyester resin for the S1 layer of the polyester film according to the present invention, for example, germanium element and phosphorus element are distilled off during the polycondensation reaction, so it is preferable to adjust the amount of addition taking into consideration the amount of distillation so as to obtain the above-mentioned amount of element.

[0060] In the method for producing the polyester resin for the S1 layer of the polyester film according to the present invention, as described above, it is preferable to adjust the contents of antimony element and metal element to satisfy the following formulae (13) to (14). In this case, it is preferable not to add antimony element except in unavoidable cases due to trace contamination caused by the reasons described above. Antimony element content (by mass) ≦ 5 ppm (13) 14ppm≦Metal element content (mass basis)≦100ppm (14) In the method for producing the polyester resin for the S1 layer of the polyester film according to the present invention, it is preferable to stir the reaction system during and after the addition of the compounds containing germanium, manganese and sodium, as the additives can be more uniformly dispersed by stirring.

[0061] In the method for producing the polyester resin constituting the S1 layer of the polyester film of the present invention, it is preferable to further deactivate the polyester resin obtained after the polycondensation reaction. It is known that the catalytic activity of the polyester resin obtained by polycondensation reaction using a germanium catalyst is deactivated by treating it under relatively mild conditions such as with hot water. By losing the catalytic activity, when the polyester resin is used in the subsequent film formation process, the thermal decomposition caused by the polycondensation catalyst is suppressed, and it is possible to obtain a polyester film with excellent heat resistance.

[0062] The deactivation treatment of the polyester resin can be carried out with various solutions such as water, phosphorus compounds, and ammonia compounds. Examples of phosphorus compounds include, but are not limited to, phosphate esters such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, triphenyl phosphate, dimethyl phosphate, diphenyl phosphate, methyl phosphate, and ethyl phosphate, and aqueous solutions or solutions of phosphorus compounds such as phosphoric acid and polyphosphoric acid, and the polyester resin is contacted with the phosphorus compounds. Examples of ammonia compounds include triethylamine, tetraethylammonium hydroxide, and tetra-n-butylammonium hydroxide. The temperature at which the polyester resin is contacted with these treatment solutions and treated is preferably 20°C or higher and 120°C or lower, more preferably 40°C or higher and 100°C or lower, and even more preferably 50°C or higher and 100°C or lower. The treatment time is preferably 30 minutes or longer and 24 hours or shorter, and more preferably 1 hour or longer and 12 hours or shorter.

[0063] In the method for producing a polyester resin according to the present invention, when the first step is produced through an esterification reaction (A) using a dicarboxylic acid and a diol, it is preferable to add a glycol component such as ethylene glycol after the esterification reaction and before adding a compound containing a sodium element. More preferably, it is added after the compound containing a manganese element and before adding a compound containing a sodium element. Since the low molecular weight substance of the polyester resin obtained by the esterification reaction has a higher degree of polymerization than the low molecular weight substance obtained by the transesterification reaction, when a sodium phosphate salt is used, it is difficult to disperse and is prone to foreign matter formation. Therefore, foreign matter formation can be suppressed by adding a glycol component such as ethylene glycol and lowering the degree of polymerization by depolymerization. At this time, if a compound containing a manganese element is present, depolymerization can be performed more efficiently.

[0064] The amount of glycol components such as ethylene glycol to be added is preferably 0.05 to 0.5 times by mol relative to the total amount of acid components, and more preferably 0.1 to 0.3 times by mol. By adjusting the amount within the above range, the polymerization time is not delayed due to a temperature drop in the polymerization system, and the sodium phosphate salt can be prevented from becoming a foreign substance.

[0065] In addition, in the production of the polyester resin used in the S1 layer of the present invention, solid-phase polymerization may be performed to obtain a polyester resin having a high molecular weight. The solid-phase polymerization is performed by heating the polyester resin under an inert gas atmosphere or under reduced pressure, although the apparatus and method are not particularly limited. The inert gas may be any gas inert to the polyester resin, such as nitrogen, helium, and carbon dioxide, but nitrogen is preferably used from the viewpoint of economy. In addition, under reduced pressure conditions, it is advantageous to achieve a higher vacuum because it shortens the time required for the solid-phase polymerization reaction, and specifically, it is preferable to maintain the pressure at 110 Pa or less. In addition, when performing a deactivation treatment, it is preferable to perform it after the solid-phase polymerization in order to perform the solid-phase polymerization efficiently.

[0066] When the polyester resin is processed into the S1 layer of the polyester film, one or more of various additives, such as colorants including pigments and dyes, lubricants, antistatic agents, flame retardants, UV absorbers, antibacterial agents, nucleating agents, plasticizers, and release agents, may be added within a range that does not impair the effects of the present invention.

[0067] Specific examples of the method for producing a polyester resin for obtaining the S1 layer of the polyester film of the present invention will be given below, but the present invention is not limited thereto.

[0068] A slurry of terephthalic acid and ethylene glycol (1.15 times the molar amount of terephthalic acid) is gradually added to an esterification reactor containing dissolved bishydroxyethyl terephthalate (BHT) at 240-260°C to allow the esterification reaction to proceed. The temperature in the reaction system is controlled to 245-250°C, and the esterification reaction is terminated when the reaction rate reaches 95%.

[0069] The esterification product thus obtained is transferred to a polymerization apparatus, and a manganese compound and a germanium compound are added. Then, ethylene glycol is added, and phosphoric acid and sodium phosphate are added. During these operations, it is preferable to keep the temperature in the system at 240 to 255°C so that the esterification product does not solidify.

[0070] Thereafter, the temperature inside the polymerization apparatus is gradually raised to 260-300°C, while the pressure inside the polymerization apparatus is gradually reduced from normal pressure to 133 Pa or less to distill off ethylene glycol. When a predetermined stirring torque is reached, the reaction is terminated, the reaction system is returned to normal pressure with nitrogen gas, and the molten polyester is discharged into cold water in the form of strands and cut to obtain a polyester resin.

[0071] The polyester resin thus obtained has excellent heat resistance and produces little gel composition or low molecular weight substances such as terephthalic acid during melt molding or processing, and can be suitably used for polyester films that require high quality, particularly for film applications such as process films, i.e., the S1 layer of the polyester film of the present invention and other layers that constitute the base layer.

[0072] Next, the method for producing the polyester film of the present invention will be described. The method for producing the polyester film of the present invention is characterized in that the S1 layer is formed using a polyester resin having a terephthalic acid volatilization amount (T) of less than 100 ppm. Here, the terephthalic acid volatilization amount (T) is the amount of terephthalic acid (mass basis) that volatilizes when heat-treated at a temperature of 290° C. for 20 minutes.

[0073] In the method for producing a polyester film of the present invention, the S1 layer is formed using a polyester resin having a terephthalic acid volatilization amount (T) of 100 ppm or less by mass. Here, the terephthalic acid volatilization amount (T) is the amount of terephthalic acid (by mass) that volatilizes when heat-treated at a temperature of 290° C. for 20 minutes, and the details of the measurement method will be described later. By making the terephthalic acid volatilization amount (T) of the polyester resin 100 ppm or less by mass, it is possible to effectively suppress minute terephthalic acid adhesion defects in the obtained polyester film. The smaller the terephthalic acid volatilization amount (T), the higher the suppression effect, and it is more preferably 50 ppm or less, and particularly preferably 30 ppm or less. The lower limit is not particularly specified, but is about 5 ppm from a technical viewpoint. The method for producing the polyester resin in order to set the volatilization amount of terephthalic acid (T) in the above-mentioned range is not particularly limited, but a preferred method is, for example, a method in which the total amount of metal elements, namely, phosphorus, sodium, manganese, antimony, and germanium, is adjusted to be within the concentration range as described above.

[0074] In the method for producing a polyester film of the present invention, when the polyester film has an S1 layer, an S2 layer, and an I layer, the S1 layer, the S2 layer, and the I layer are formed using a polyester resin that satisfies all of the following (7) to (9). Ts1 <Ti (7) Ts2 <Ti (8) Ti≦350ppm (9) Ts1: Volatilization amount of terephthalic acid from the polyester resin constituting the S1 layer (T) Ts2: Volatilization amount of terephthalic acid from the polyester resin that constitutes the S2 layer (T) Ti: Volatilization amount of terephthalic acid from the polyester resin that constitutes the I layer (T) Here, the amount of volatilized terephthalic acid (T) is the amount of terephthalic acid (mass basis) that volatilizes when heat-treated at a temperature of 290°C for 20 minutes, and when the I layer is composed of multiple layers, the amount of volatilized terephthalic acid (T) is calculated as the weighted average value of the multiple layers.

[0075] When the base layer of the polyester film to be manufactured has a laminated structure, the terephthalic acid volatilization amount of the S1 layer and the S2 layer constituting the two outermost layers is adjusted to be equal to or less than the terephthalic acid volatilization amount of the I layer forming the middle part, so that even if the terephthalic acid volatilization amount of the polyester resin forming the I layer is high, it is possible to effectively suppress minute terephthalic acid adhesion defects. Therefore, for example, it is possible to contain recycled raw materials in the I layer, or to use a polyester resin with a large terephthalic acid volatilization amount in order to express other functions and characteristics. From the above viewpoint, the terephthalic acid volatilization amount (Ti) of the polyester resin constituting the I layer is preferably 350 ppm or less, more preferably 200 ppm or less, and even more preferably 150 ppm or less. There is no particular restriction on the lower limit of Ti, but it is 5 ppm from the viewpoint of feasibility. In addition, Ts1 and Ts2 are not particularly limited as long as they are below Ti, but are preferably 100 ppm or less, and even more preferably 80 ppm or less. There is no particular lower limit for Ts1 or Ts2, but these are also set at 5 ppm from the standpoint of feasibility.

[0076] In the method for producing a polyester film of the present invention, when the polyester film has an S1 layer, an S2 layer, and an I layer, it is preferable that the melt resistivity of the polyester resin constituting the S1 layer and the polyester resin constituting the S2 layer are both higher than 10.0 MΩ·cm, and the melt resistivity of the polyester resin constituting the I layer is 10.0 MΩ·cm or less. One of the factors that affect the thickness unevenness of the polyester film obtained by the melt film-forming method is the electrostatic applicability when the molten sheet-like material for obtaining the base layer is cooled and solidified in a cast drum. This electrostatic applicability can be evaluated by the melt resistivity when the base layer of the finally obtained polyester film is melted, and can also be substituted by the melt resistivity of the molten polyester resin that is the raw material of the base layer.

[0077] The melt resistivity is the volume resistivity of the heat-melted polyester resin. From the above viewpoint, the melt resistivity of the polyester resin constituting the I layer of the polyester film of the present invention is preferably 10.0 MΩ·cm or less, more preferably 5.0 MΩ·cm or less. When the melt resistivity of the I layer is 10.0 MΩ·cm or less, the electrostatic applicability during cooling and solidification in the cast drum is good, so that the thickness unevenness of the obtained polyester film is suppressed, and the film production speed can be increased to improve productivity. In addition, the lower limit of the melt resistivity of the I layer is not particularly limited, but is 0.1 MΩ·cm from the viewpoint of feasibility.

[0078] The method of making the melt resistivity of the I layer within the above range includes, but is not limited to, making the metal element content or phosphorus element content in the polyester resin that is the raw material of the I layer within the above-mentioned preferred range, and adding particles or compounds that are responsible for electrical conduction to the raw material. However, if the metal element content in the raw material is increased, as described above, the terephthalic acid volatilization amount (T) of the obtained polyester film may increase, or the generation of foreign matter due to gelation may be induced. Therefore, it is preferable to apply an ionic substance that is not based on metal, and for example, sulfonium compounds, phosphonium compounds, ammonium compounds, imidazolium compounds, pyridinium compounds, and pyrrolidinium compounds can be selected as cationic substances, and sulfonate compounds, phosphate compounds, sulfate compounds, acetate compounds, imide compounds, and the like can be selected as anionic substances. In particular, neutralized salts of phosphonium compounds and sulfonate compounds are preferable.

[0079] In the method for producing a polyester film of the present invention, when the polyester film has an S1 layer, an S2 layer, and an I layer, it is preferable that the melt resistivity values ​​of the polyester resin constituting the S1 layer and the polyester resin constituting the S2 layer are both higher than 10.0 MΩ·cm. The S1 layer and the S2 layer constitute the outermost layer of the polyester film base layer, and in order to reduce defects derived from terephthalic acid, it is effective to reduce the amount of terephthalic acid volatilized from this layer. In order to reduce the melt resistivity value of the polyester resin, it is necessary to make a metal element contained therein or to add an ionic substance, as described above. If such a method is used, the amount of terephthalic acid volatilized (T) may increase, or the added ionic substance may contaminate the film production process such as the transport roll, causing defects. By maintaining the melt resistivity values ​​of the polyester resin constituting the S1 layer and the polyester resin constituting the S2 layer both higher than 10.0 MΩ·cm, the above problems can be alleviated.

[0080] Next, the method for producing the polyester film of the present invention will be described taking as an example a single-layer film using polyethylene terephthalate (PET) as the polyester forming the S1 layer, but the method is not limited thereto.

[0081] The PET pellets with an intrinsic viscosity of 0.5 to 0.8 dl / g constituting the S1 layer are vacuum dried, fed into an extruder and melted at 260 to 300°C. After removing foreign matter with a filter, the pellets are extruded into a sheet from a T-shaped die, and wrapped around a mirror-finished casting drum with a surface temperature of 10 to 60°C using an electrostatic casting method, and cooled and solidified to produce an unstretched PET film. This unstretched film is stretched 2.5 to 5.0 times in the machine direction between rolls heated to 70 to 100°C to obtain a uniaxially stretched film. Note that some or all of the PET pellets may contain recycled raw materials, which will be described later.

[0082] A water-based coating agent constituting a functional layer is applied to at least one side of this uniaxially stretched film. Then, the widthwise ends of the uniaxially stretched film coated with the water-based coating agent are held by clips of a tenter device and introduced into a drying zone, where the coating agent is dried and then heated at a temperature of 70 to 150 ° C., and then continuously stretched 2.5 to 5.0 times in the transverse direction in a heating zone of 70 to 150 ° C., and then heat-treated for 5 to 40 seconds in a heating zone of 200 to 240 ° C., and passed through a cooling zone of 100 to 200 ° C. to obtain a polyester film in which a functional layer is laminated on a substrate layer in which crystal orientation has been completed. During the heat treatment, a 3 to 12% relaxation treatment may be performed as necessary. In the above example, the biaxial stretching is performed by sequential longitudinal and transverse stretching, but the stretching may be performed by simultaneous biaxial stretching, and after longitudinal and transverse stretching, the stretching may be performed again in either the longitudinal or transverse direction. However, in the case of simultaneous biaxial stretching, since it is not possible to apply a water-based coating material to a uniaxially stretched film, when an in-line coating method is employed, it is advisable to apply a water-based coating material to an unstretched film.

[0083] Thereafter, both ends in the width direction held by the clips are cut and removed from the obtained polyester film, and the film is cut to a desired width and wound up. Note that the cutting and removal of both ends in the width direction and the cutting to a desired width can be performed by a device capable of cutting a traveling film parallel to the longitudinal direction, such as a known slitter.

[0084] In addition, in obtaining the recovered raw material, the method of removing the functional layer of the polyester film includes a method of physically scraping off the surface and a method of dissolving and peeling off with a cleaning agent, but the latter cleaning method using a cleaning agent is preferred from the viewpoint of suppressing the remaining of the functional layer and enabling uniform removal. The cleaning agent to be used is not particularly limited, but it is preferable to use an alkaline cleaning agent because it acts on the surface of the polyester film and partially decomposes it, thereby enabling efficient removal of the functional layer formed on the film. The alkaline cleaning agent may be either an inorganic alkalizing agent or an organic alkalizing agent, but inorganic alkalizing agents are preferred in terms of removal efficiency.

[0085] Examples of inorganic alkalizing agents include aqueous solutions of alkali metal silicates such as sodium hydroxide, potassium hydroxide, rubidium hydroxide, cesium hydroxide, calcium hydroxide, barium hydroxide, etc., sodium carbonate, potassium carbonate, trisodium phosphate, sodium pyrophosphate, sodium tripolyphosphate, sodium tetrapolyphosphate, tripotassium phosphate, potassium pyrophosphate, potassium tripolyphosphate, sodium orthosilicate, sodium metasilicate, and potassium silicate, etc., which may be used alone or in appropriate mixtures. Furthermore, cleaning with these components may be carried out multiple times, and in that case, the type of cleaning agent may be changed appropriately.

[0086] The concentration of the alkaline aqueous solution used in the removal step is preferably pH 10 or more. For example, the concentration of sodium hydroxide is generally 0.1 mass% or more, but is preferably 0.1 to 30 mass%, and more preferably 0.4 to 20 mass%. If the concentration is too low, problems such as insufficient removal of the functional layer or too much removal time may occur. If the concentration is too high, decomposition of the polyester base material may proceed excessively. In addition, the temperature of the alkaline aqueous solution is preferably 50°C or more from the viewpoint of shortening the removal time and improving the removal efficiency, and is more preferably 70°C or more and 100°C or less.

[0087] In addition, in order to promote the penetration of the alkalizing agent into the interface between the polyester film and the functional layer, alcohols such as methyl alcohol, ethyl alcohol, propyl alcohol, butyl alcohol, benzyl alcohol, ethylene glycol monomethyl ether, diethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol, and diethylene glycol, as well as various surfactants such as nonionic, anionic, and cationic surfactants can also be used. As nonionic surfactants, for example, polyethylene glycol ethers, particularly polyethylene glycol ethers of higher alcohols and polyethylene glycol ethers of alkylphenols, are preferably used. Furthermore, a method of increasing hydrophilicity by subjecting the film surface to a corona discharge treatment or plasma discharge treatment in advance is also effective in promoting interfacial peeling.

[0088] In order to reduce the amount of the alkalizing agent remaining in the recovered raw material, it is preferable to wash with water after washing with an alkaline aqueous solution. If the alkalizing agent remains in the recovered raw material, the amount of foreign matter may increase, the deterioration of the polyester resin may be accelerated, and the amount of gelled matter may increase. In particular, when sodium hydroxide is used as the alkalizing agent, it is preferable to wash with water, since it affects the amount of sodium element remaining mainly in the base layer (especially the S1 layer and S2 layer).

[0089] The polyester film recycling method includes the so-called material recycling method, in which the recovered, crushed, and washed film is used as it is, or remelted and pelletized, and the so-called chemical recycling method, in which the film is depolymerized to the monomer or oligomer level and then polycondensed again to regenerate it, but is not particularly limited in the present invention. However, the material recycling method is preferred from the viewpoint of the reduction rate of energy consumption and CO2 generation and the cost of recycling. With the polyester film of the present invention, it is possible to provide a polyester film with few defects derived from terephthalic acid even if the material recycling is repeated. In addition, the recycled raw material may be subjected to solid phase polymerization in order to increase the intrinsic viscosity IV of the polyester resin. EXAMPLES

[0090] The present invention will now be described in more detail with reference to examples, but the present invention is not limited to these examples.

[0091] [Measurement methods for physical properties and evaluation of various characteristics] Measurement of physical properties and evaluation of various characteristics were carried out by the following methods.

[0092] (1) Quantitative determination of germanium, manganese, phosphorus, sodium, antimony, and metal elements in polyester resin and polyester film (base layer) 1 g of the sample was placed on a platinum dish, melted and carbonized with an electric heater, and then completely incinerated in an electric furnace (700°C) for 1.5 hours. The incinerated material was then dissolved in 1 mL of concentrated hydrochloric acid, and pure water was added to make a 10% hydrochloric acid solution, which was used as the measurement sample. The above solution was used as the measurement sample and quantified by atomic absorption spectrometry (frame: acetylene-air, germanium element only acetylene-dinitrogen monoxide). The atomic absorption spectrophotometer used was the "ZA-3300" manufactured by Hitachi High-Tech Science Co., Ltd. In addition, in the case of polyester films with functional layers, the functional layers were removed using the following method, and then the measurement sample was used. In order to measure the amount of metal components contained in the S1 and S2 layers of the film, the PET resin of the S1 and S2 layers was scraped off from the surface of the substrate, and the measurement was performed using a sample.

[0093] Since the film before the functional layer was removed did not contain potassium element, when potassium element was detected in this measurement, it was determined to be derived from residues remaining after the functional layer was removed, and was therefore excluded from quantification.

[0094] [Removal of functional layer] The polyester film was cut into 2.0 cm squares, placed in a 7% by mass potassium hydroxide aqueous solution (pH: 14), and washed with stirring for 1 hour at a temperature of 85° C. After washing, the sample was washed twice with pure water for 10 minutes with stirring to obtain a sample from which the functional layer had been removed.

[0095] (2) Intrinsic viscosity (IV) of polyester resin The polyester resin or polyester film was dissolved in 100 mL of orthochlorophenol (solution concentration C = 1.2 g / mL), and the viscosity of the solution at 25°C was measured using an Ostwald viscometer. The viscosity of the solvent was also measured in the same manner. Using the obtained solution viscosity and solvent viscosity, [η] was calculated according to the following formula, and the obtained value was taken as the intrinsic viscosity (IV). ηsp / C=[η]+K[η] 2 C (Here, ηsp = (solution viscosity / solvent viscosity)-1, and K is the Huggins constant (assumed to be 0.343).)

[0096] (3) Melt resistivity of polyester resin The polyester resin used to form each layer was vacuum dried at 180° C. for 3 hours and then melted at 290° C. An electrode was prepared by sandwiching a Teflon (registered trademark) spacer between two copper plates, and this electrode was submerged in the molten resin. A voltage of 5000 V (V) was applied between the electrodes, and the voltage (V') was measured, and the melt resistivity (ρ) was calculated from the following formula. ρ(Ω cm)=V S R / (I V') In the formula, V is the applied voltage (V), S is the electrode area (cm 2 ), R: resistor resistance (Ω), I: distance between electrodes (cm), V': measured voltage (V).

[0097] (4) Volatilization of terephthalic acid from polyester resin The polyester resin pellets were vacuum dried at 160°C for 8 hours under a reduced pressure of 3 kPa. The dried sample was placed in an impinger and treated at 290°C for 20 minutes under a nitrogen stream. The generated volatile components were collected in methanol, and the resulting solution was concentrated in an evaporator and then filtered through a disk filter with a pore size of 0.45 μm to obtain a sample solution. This sample solution was measured by high performance liquid chromatography (Shimadzu Corporation: Nexera), and the terephthalic acid content (ppm) relative to the mass of the polyester resin was determined using a calibration curve created from a terephthalic acid standard solution.

[0098] (5) Evaluation of foreign matter in polyester resin 0.1 mg of polyester resin was sandwiched between two cover glasses on a hot plate heated to 290°C and melted to produce a preparation on which a polymer thin film was formed. This preparation was observed under an optical microscope (Olympus Corporation: BX50, 400x, dark field) and all observable light spots were counted. The number of light spots obtained was judged according to the following criteria, with A and B being pass and C being fail. A: The number of light spots was 0 to 5 per 0.1 mg. B: There were 6 to 9 light spots per 0.1 mg. C: There were 10 or more light spots per 0.1 mg.

[0099] (6) Number of foreign particles with terephthalic acid on polyester film While the polyester film was being unwound, defects of 100 μm or more in size were detected by a camera using the reflection type defect detection system described below. In the obtained camera image, defects in the form of a cluster of minute defects, which are characteristic of terephthalic acid adhesion defects, were sampled, and the number of defects that could be identified as terephthalic acid was counted using a Fourier transform infrared microscope ("NICOLET" (registered trademark) 6700 manufactured by Thermo Fisher Scientific Co., Ltd. and a CONTINUUM infrared microscope), and the number of defects per unit area (1 m 2 The number of pieces per 100 was calculated. Distance between light source and film: 100mm Camera-film distance: 760mm ·Reflection angle: 15° Camera resolution: 15μm Detection speed: 10m / min Detection area: 100m 2 The number of terephthalic acid adhesion defects obtained was judged according to the following criteria, with A and B being pass and C being fail. A: Terephthalic acid adhesion defects are 0 / m 2 More than 0.05 pieces / m 2 It was less than. B: Terephthalic acid adhesion defects are 0.05 pieces / m 2 More than 0.15 pieces / m 2 It was less than. C: Terephthalic acid adhesion defects are 0.15 / m 2 That was all.

[0100] (7) Number of internal defects in polyester film One side of the polyester film was filled in with a black oil-based pen (Teranishi Chemical Industry Co., Ltd. Magic Ink No. 500 Black M500-T1) to prepare a sample. From the opposite side to the filled side, a 10 mm wide × 25 mm long range of the sample was observed at 200x magnification (eyepiece 20x, objective lens 10x) using a Keyence laser microscope VK-X100, and the number of foreign objects with a major axis size of 10 μm or more was confirmed. The number of internal defects was evaluated according to the following criteria, with C being a failure. A: The number of foreign objects is 10 / 250 mm 2 The results were as follows. B: 10 foreign objects / 250mm 2 Exceeding 30 pieces / 250mm 2 The results were as follows. C: 30 foreign objects / 250mm 2 exceeded.

[0101] [Reference Example 1] Preparation of polyester resin 1 A slurry consisting of 86 parts by mass of terephthalic acid and 37 parts by mass of ethylene glycol (1.15 times the molar amount relative to terephthalic acid) was gradually added to an esterification reactor containing 105 parts by mass of bishydroxyethyl terephthalate (hereinafter referred to as BHT) melted at 250°C, and the esterification reaction was allowed to proceed. The temperature in the reaction system was controlled to be 245 to 250°C, and the esterification reaction was terminated when the reaction rate reached 95%.

[0102] 105 parts by mass (corresponding to 100 parts by mass of PET) of BHT was charged in a molten state from the esterification reactor into the polymerization apparatus, and the temperature was set to 255°C. An ethylene glycol solution of manganese acetate tetrahydrate (23 ppm as manganese element relative to the mass of polyester resin) and germanium dioxide (45 ppm as germanium element relative to the mass of polyester resin) were added. Then, an ethylene glycol solution of phosphoric acid (19 ppm as phosphorus element relative to the mass of polyester resin) and sodium dihydrogen phosphate dihydrate (14 ppm as sodium element relative to the mass of polyester resin, 19 ppm as phosphorus element) was added. The germanium dioxide was completely dissolved in a 20% by mass aqueous solution of tetraethylammonium hydroxide, and then an ethylene glycol solution to which ethylene glycol was added was used.

[0103] Thereafter, the temperature inside the polymerization apparatus was gradually increased to 290°C, while the pressure was reduced from normal pressure to 133 Pa or less, and the polymerization reaction was allowed to proceed until a predetermined stirring torque was observed at 290°C. After the polymerization reaction was completed, the reaction system was returned to normal pressure with nitrogen gas, and the molten polyester in the polymerization apparatus was discharged in the form of strands into a water tank, cooled, and then cut to obtain pellet-shaped polyester resin 1. The properties of the obtained polyester resin are shown in Table 1.

[0104] [Reference Example 2] Preparation of polyester resin 2 A slurry consisting of 86 parts by mass of terephthalic acid and 37 parts by mass of ethylene glycol (1.15 times the molar amount relative to terephthalic acid) was gradually added to an esterification reactor containing 105 parts by mass of bishydroxyethyl terephthalate (hereinafter referred to as BHT) melted at 250°C, and the esterification reaction was allowed to proceed. The temperature in the reaction system was controlled to be 245 to 250°C, and the esterification reaction was terminated when the reaction rate reached 95%.

[0105] 105 parts by mass (corresponding to 100 parts by mass of PET) of BHT was charged in a molten state from the esterification reactor into the polymerization apparatus, and the temperature was set to 255°C. An ethylene glycol solution of manganese acetate tetrahydrate (23 ppm as manganese element relative to the mass of polyester resin) and germanium dioxide (45 ppm as germanium element relative to the mass of polyester resin) were added. Next, an ethylene glycol solution of phosphoric acid (19 ppm as phosphorus element relative to the mass of polyester resin) and sodium dihydrogen phosphate dihydrate (14 ppm as sodium element and 19 ppm as phosphorus element relative to the mass of polyester resin) was added, and then an ethylene glycol slurry of colloidal silica with an average particle size of 1 μm was added so that the silica content was 0.1% by mass relative to the polyester resin. The germanium dioxide was completely dissolved in a 20% by mass aqueous solution of tetraethylammonium hydroxide, and then an ethylene glycol solution to which ethylene glycol was added was used.

[0106] Thereafter, the temperature inside the polymerization apparatus was gradually increased to 290°C, while the pressure was reduced from normal pressure to 133 Pa or less, and the polymerization reaction was allowed to proceed until a predetermined stirring torque was observed at 290°C. After the polymerization reaction was completed, the reaction system was returned to normal pressure with nitrogen gas, and the molten polyester in the polymerization apparatus was discharged in the form of strands into a water tank, cooled, and then cut to obtain pellet-shaped polyester resin 2. The properties of the obtained polyester resin are shown in Table 1.

[0107] [Reference Examples 3 to 8, 12 to 16] Preparation of polyester resins 3 to 8 and 12 to 16 Polyester resins 3 to 8 and 12 to 16 were obtained in the same manner as in Reference Example 2, except that the amounts of germanium, manganese, sodium, and phosphorus in the polyester resin were adjusted as shown in Tables 1 and 2. The properties of the obtained polyester resins are shown in Tables 1 and 2.

[0108] [Reference Example 9] Preparation of polyester resin 9 Polyester resin 10 was obtained in the same manner as in Reference Example 2, except that an ethylene glycol solution of tetra-n-butoxytitanium (10 ppm as titanium element relative to the mass of the polyester resin composition) was added instead of germanium dioxide. The properties of the obtained polyester resin are shown in Table 1.

[0109] [Reference Example 10] Preparation of polyester resin 10 Polyester resin 10 was obtained in the same manner as in Reference Example 2, except that an ethylene glycol slurry of diantimony trioxide was added instead of germanium dioxide so that the antimony content was 85 ppm relative to the mass of the polyester resin composition, the amounts of manganese, sodium, and phosphorus were adjusted to be as shown in Table 2, and an ethylene glycol solution of an equimolar mixture of paratoluenesulfonic acid and tetrabutylphosphonium hydroxide (20 ppm relative to the mass of the polyester resin composition) was added after the addition of phosphoric acid and sodium dihydrogen phosphate dihydrate. The properties of the obtained polyester resin are shown in Table 2.

[0110] [Reference Example 11] Preparation of polyester resin 11 Polyester resin 11 was obtained in the same manner as in Reference Example 2, except that an ethylene glycol slurry of diantimony trioxide was added instead of germanium dioxide so that the antimony content was 100 ppm relative to the mass of the polyester resin composition, and the amounts of manganese, sodium, and phosphorus added were adjusted as shown in Table 2. The properties of the obtained polyester resin are shown in Table 2.

[0111] [Reference Example 17] Preparation of polyester resin 17 Polyester resin 17 was obtained in the same manner as in Reference Example 2, except that after the addition of phosphoric acid and sodium dihydrogen phosphate dihydrate, an equimolar ethylene glycol solution of paratoluenesulfonic acid and tetrabutylphosphonium hydroxide (60 ppm as phosphorus element relative to the mass of the polyester resin composition) was added. The properties of the obtained polyester resin are shown in Table 2.

[0112] Reference Example 18 Preparation of long-chain alkyl resin (X) A 25 mL pressure-resistant glass polymerization ampoule was charged with methyl methacrylate (MMA) (Kanto Chemical Co., Ltd.), α,α'-azobisisobutyronitrile (AIBN) (Kanto Chemical Co., Ltd.) as a polymerization initiator, cumyl dithiobenzoate (CDB) as a RAFT agent, and toluene as a solvent, with a weight ratio (g) of MMA / CDB / AIBN / toluene = 2.92 / 0.03 / 0.007 / 2.27. Next, the mixed solution in the ampoule was degassed twice by the freeze degassing method, and then the ampoule was sealed and heated in an oil bath at 100°C for 18 hours to obtain polymerization solution 1. Next, docosyl acrylate, AIBN as a polymerization initiator, and toluene as a solvent were added to the reaction solution in the ampoule at a weight ratio (g) of docosyl acrylate / AIBN / toluene = 1.37 / 0.003 / 1.3, and the mixture was frozen and degassed twice, after which the ampoule was sealed and heated at 100 ° C for 48 hours. Then, polymerization solution 1 was dropped into 20 times the mass of hexane and stirred to precipitate a solid. The resulting solid was filtered and vacuum dried overnight at 40 ° C to obtain a long-chain alkyl resin (X) having an alkyl group with 22 carbon atoms. The resulting long-chain alkyl resin (X) was emulsified as follows to obtain an aqueous resin emulsion. 375 g of water was placed in a 1 L homomixer, and 45 g of polyoxyethylene nonylphenyl ether, 30 g of polyoxyethylene polyoxypropylene glycol, 200 g of long-chain alkyl resin (X), and 150 g of toluene were added in that order, and the mixture was heated to 70 ° C and stirred uniformly. This mixture was transferred to a pressure homogenizer and emulsified, after which the pressure was reduced under heating to distill off the toluene, yielding a long-chain alkyl resin (X).

[0113] [Reference Example 19] Preparation of acrylic resin (Y) Methyl methacrylate (α), hydroxyethyl methacrylate (β), and urethane acrylate oligomer (manufactured by Negami Chemical Industries, Ltd., "Art Resin" (registered trademark) UN-3320HA, number of acryloyl groups is 6) (γ) were charged in a mass ratio of (α) / (β) / (γ)=94 / 1 / 5 in a stainless steel reaction vessel, and 2 parts by mass of sodium dodecylbenzenesulfonate was added as an emulsifier to a total of 100 parts by mass of (α) to (γ) and stirred to prepare mixed solution 1. Next, a reaction apparatus equipped with a stirrer, a reflux condenser, a thermometer, and a dropping funnel was prepared. 60 parts by mass of the above mixed solution 1, 200 parts by mass of isopropyl alcohol, and 5 parts by mass of potassium persulfate as a polymerization initiator were charged in a reaction apparatus and heated to 60°C to prepare mixed solution 2, which was then kept heated at 60°C for 20 minutes. Next, mixed solution 3 consisting of 40 parts by mass of mixed solution 1, 50 parts by mass of isopropyl alcohol, and 5 parts by mass of potassium persulfate was prepared. Then, mixed solution 3 was dropped into mixed solution 2 over 2 hours using a dropping funnel to prepare mixed solution 4. Then, mixed solution 4 was heated to 60°C and held for 2 hours. After cooling the obtained mixed solution 4 to 50°C or less, it was transferred to a container equipped with a stirrer and a pressure reducing device. 60 parts by mass of 25% ammonia water and 900 parts by mass of pure water were added thereto, and isopropyl alcohol and unreacted monomers were collected under reduced pressure while heating to 60°C, and an acrylic resin (Y) dispersed in pure water was obtained.

[0114] [Reference Example 20] Preparation of recycled raw material The polyester film was crushed to a size of 0.5 cm to 3.0 cm, and then placed in a 5% by mass aqueous solution of sodium hydroxide (pH: 14), and washed at a temperature of 85°C for 1 hour while stirring. After washing, the crushed material was washed with water and dried to obtain a washed crushed polyester film. The crushed material obtained was melted in a twin-screw extruder equipped with a vacuum vent, extruded from a nozzle into a strand shape, cooled in a water tank, and cut with a cutter to obtain recycled polyester pellets (raw material).

[0115] [Reference Example 21] Method for producing polyester film The polyester resin raw material was dried in a vacuum at 160°C for 4 hours, and then fed to extruder 1 and melt-extruded at 285°C. The raw material was filtered through a filter with an average opening of 5μm made by sintering and compressing stainless steel fibers, and then through a filter made of sintered stainless steel powder with an average opening of 14μm, to obtain a molten polyester resin (A). The polyester resin raw material dried in the same manner was fed to extruder 2 and melt-extruded at 285°C. The raw material was then filtered through a filter with an average opening of 5μm made by sintering and compressing stainless steel fibers, and then through a filter made of sintered stainless steel powder with an average opening of 14μm, to obtain a molten polyester resin (B). Next, using a lamination device, the molten resin was laminated in the thickness direction from the outermost layer to a thickness ratio of 2:34:2, so that (A) / (B) / (A) would be obtained, and then extruded from a T-shaped die into a sheet, and wrapped around a mirror-finished casting drum with a surface temperature of 25°C at a casting speed of 30m / min using an electrostatic casting method, and cooled and solidified to obtain an unstretched film. This unstretched film was preheated to 80°C with a preheating roll, and then stretched 3.5 times in the longitudinal direction by utilizing the difference in peripheral speed between the rolls while heating it to 95°C from above and below using a radiation heater, and then cooled to 25°C with a cooling roll to obtain a uniaxially oriented (uniaxially stretched) film. Next, the following aqueous coating liquid was measured using a metalling wire bar (#4) and applied onto one surface of the uniaxially stretched film so that the final functional layer thickness was 50 nm.

[0116] <Coating fluid> The coating solution was prepared so that the solid content ratio of each coating agent was as follows, with a solid content concentration of 3.3% by mass. Long-chain alkyl resin (X) obtained in Reference Example 18: 25% by mass Acrylic resin (Y) obtained in Reference Example 19: 45% by mass Melamine-based crosslinking agent ("Nicalac" (registered trademark) MW12LF, manufactured by Sanwa Chemical Co., Ltd.): 30% by mass (solid content equivalent) The uniaxially stretched film coated with the water-based coating agent was held at both ends in the width direction by clips and transported to an oven, where it was dried and preheated at an atmospheric temperature of 120°C. It was then continuously stretched 4.0 times in the width direction in a 120°C stretching zone. The obtained biaxially oriented (biaxially stretched) film was then heat-treated for 10 seconds in a 230°C heating zone, and then cooled from 230°C to 120°C while undergoing a 5% relaxation treatment, and then cooled to 50°C. The two ends in the width direction were then removed and the film was wound up to obtain a polyester film with a thickness of 38μm. The thickness direction of this polyester film was structured in the order of release layer (functional layer) / S1 layer / I layer / S2 layer, and the thickness of the base layer was S1 layer / I layer / S2 layer = 2μm / 34μm / 2μm (total 38μm). In addition, when the base layer is composed of multiple layers, the outermost layers on both sides have a thickness of 1 μm or more, satisfy all of the above (1) to (5), and are layers mainly composed of polyester resin, the S1 layer and the S2 layer can be arbitrarily determined. In this Reference Example 21, in such a case, the S1 layer was arbitrarily selected, and a functional layer was formed on its surface.

[0117] [Example 1] Using the polyester resin composition shown in Table 3, a polyester film having a release layer on one surface (S1 layer side surface) of the polyester film substrate was obtained by the method of Reference Example 21. For the I layer, polyester resin 17, polyester resin 2, and self-recovered raw material were mixed at 5 mass%, 45 mass%, and 50 mass%, respectively. The self-recovered raw material here refers to a recovered raw material obtained by chipping the film edges and winding core parts that were no longer needed when producing this polyester film, and the film peeled off after use as a process film, after removing the functional layer by the method of Reference Example 20. The properties of the obtained polyester film are shown in Table 6.

[0118] [Examples 2 to 16, Comparative Examples 1 to 9] A polyester film was obtained in the same manner as in Example 1, except that the thicknesses of the layers constituting the polyester resin and the polyester base material were as shown in Tables 3 to 5. The properties of the obtained polyester film are shown in Tables 6 to 8. The base layer of the polyester film was a single layer structure using only extruder 1 in Example 14, a two-layer structure of (A) / (B) in a lamination device in Example 11, and a three-layer structure of (A) / (B) / (C) in Example 12 using a lamination device similar to that in Example 1 but using an additional extruder 3. In Example 16, the S1 layer and the S2 layer were made by mixing polyester resin 2 and polyester resin 11 at 95% by mass and 5% by mass, respectively.

[0119] In Examples 11 and 14, the electrostatic casting property was deteriorated, so the casting speed was reduced to 20 m / min to produce the film, but the quality was acceptable. In Examples 11 and 12, since the S1 layer constituting the surface of the substrate on which the release layer was formed did not contain any lubricant, a very smooth release surface could be formed, which was suitable for high-definition displays and ultra-small MLCCs with thin interlayer insulation layers, and the S2 layer side surface was given appropriate slipperiness by the lubricant particles, which made it easy to handle. Furthermore, in Example 12, the S1 layer, S2 layer, and I layer were each made of independent raw material compositions, so that even if a large amount of self-recovered raw material was used in the I layer, which is the intermediate layer, the adhesion defects of small terephthalic acid could be reduced, making it particularly excellent as a release film for processing.

[0120] [Table 1]

[0121] [Table 2]

[0122] [Table 3]

[0123] [Table 4]

[0124] [Table 5]

[0125] [Table 6]

[0126] [Table 7]

[0127] [Table 8] [Industrial Applicability]

[0128] According to the polyester film and the manufacturing method thereof of the present invention, a clean polyester film with few defects of adhesion of terephthalic acid can be obtained, and the film can be suitably used as a process film used in the process of manufacturing high-quality display members and electronic material members, where even minute foreign matter can induce fatal defects in the product. Furthermore, even when a recycled raw material obtained by regenerating a film is used, adhesion of terephthalic acid can be effectively suppressed, so the film can be suitably used as a high-quality product with reduced environmental load, which has been in increasing demand in recent years.

Claims

1. The substrate layer has a polyester resin as a main component. A layer having a thickness of 1 μm or more, satisfying all of the following (1) to (5), and containing a polyester resin as a main component is 1 When the substrate layer is formed as a layer, at least one of the outermost layers of the substrate layer is the S 1 1. A polyester film comprising a layer. 15 ppm≦Phosphorus element content (by mass)≦80 ppm (1) 4 ppm≦Sodium element content (by mass)≦40 ppm (2) 5 ppm≦Manganese element content (by mass)≦40 ppm (3) Antimony element content (by mass) ≦ 5 ppm (4) 14ppm≦Metal element content (mass standard)≦100ppm (5)

2. The S 1 2. The polyester film according to claim 1, wherein the layer satisfies the following (6): 5 ppm≦Germanium element content (by mass)≦80 ppm (6)

3. 3. The polyester film according to claim 1, wherein at least a part of the phosphorus element is derived from phosphoric acid and sodium phosphate.

4. The base layer is 1 layer, the S 1 The layer (S 2 layer), 2 The polyester film according to claim 1 or 2, wherein the layer satisfies all of the above (1) to (5).

5. The base layer is 1 layer, the S 1 The layer (S 2 layer), and the S 1 layer and the S 2 3. The polyester film according to claim 1, which comprises one or more layers (I layers) located between the layers.

6. The polyester film according to claim 5 , wherein at least one of the I layers contains a recycled material containing a polyester resin as a main component.

7. 7. The polyester film of claim 6, wherein the recycled materials comprise self-recycled materials.

8. The polyester film according to claim 1 , further comprising a functional layer on at least one surface of the base layer.

9. A method for producing the polyester film according to claim 1 or 2, comprising the steps of: producing the polyester film according to claim 1 or 2 by using a polyester resin having a volatilized amount (T) of terephthalic acid of less than 100 ppm; 1 A method for producing a polyester film by forming a layer. Here, the volatilized amount of terephthalic acid (T) is the amount (by mass) of terephthalic acid volatilized when heat-treated at a temperature of 290° C. for 20 minutes.

10. A method for producing the polyester film according to claim 5, comprising the steps of: producing the polyester film according to claim 5 by using a polyester resin that satisfies all of the following (7) to (9) and 1 layer, the S 2 A method for producing a polyester film, comprising forming the I layer and the I layer. Ts 1 <Three (7) Ts 2 <Three (8) Ti≦350 ppm (9) Ts 1 : The above S 1 Volatilization amount of terephthalic acid from the polyester resin constituting the layer (T) Ts 2 : The above S 2 Volatilization amount of terephthalic acid from the polyester resin constituting the layer (T) Ti: volatilization amount of terephthalic acid from the polyester resin constituting the I layer (T) Here, the volatilized amount of terephthalic acid (T) is the amount (mass basis) of terephthalic acid volatilized when heat-treated at a temperature of 290° C. for 20 minutes, and when the I layer is composed of a plurality of layers, the volatilized amount of terephthalic acid (T) is calculated as the weighted average value of the layers.

11. The S 1 The polyester resin constituting the layer and the S 2 The method for producing a polyester film according to claim 10, wherein the melt resistivity of each of the polyester resins constituting the I layer is higher than 10.0 MΩ·cm, and the melt resistivity of the polyester resin constituting the I layer is 10.0 MΩ·cm or less.

Citation Information

Patent Citations

  • Polyester resin composition and polyester film including the same

    JP2022089784A

  • Biaxially oriented polyester film and laminate

    JP2023015002A

  • Power assistance control device and power assistance control method for power-assisted bicycle, and automatic speed change method therefor

    WO2016177084A1

  • Method for producing polyester-based thermoplastic film, polyester-based thermoplastic film, and method for inspecting polyester-based thermoplastic film or resinous material therefor

    WO2018092414A1